EFEKTIVITAS PEMBELAJARAN DENGAN MENGGUNAKAN TEKNIK PEMBELAJARAN DESKRIPSI, INTERPRETASI DAN EVALUASI DI KELAS XI MADRASAH ALIYAH NEGERI BARUMUN TENGAH - Nasution, Nurhidayah Fithriyah (Institut Pendidikan Tapanuli Selatan, 2016)
This reasearch was aimed to know The Effectiveness of Learning by Using Description, Interpretation, and Evaluation Learning Technique in Excretion Syystem in Humans Subject Matter of Student in Class XI Madrasah Aliyah Negeri Barumun Tengah. This research was conducted in May to July 2016 in Madrasah Aliyah Negeri Barumun Tengah. The population in this research was all students class XI Madrasah Aliyah Negeri Barumun Tengah totalling 68 students which was consisted of two classes, XI1 and XI2.  The sample in this research was one class totalling 35 students.The technique sampling was random sampling. The observation was conducted to 35 students by using multiple choice test totalling 25 items.The success indicator of this reasearch were: the average value of learning outcomes, learning mastery, and the mastery of indicator achievement. The research result showed that the average value of studentâs learning outcomes which was taught by description, interpretation, and evaluation learning technique was 7.6 (good category) where the standard deviation was 15.5. Studentâs learning mastery in The Excretion System in Humans subject matter in Class XI Madrasah Aliyah Negeri Barumun Tengah was 91.42% while 8.58% has not achieve the learning mastery. Based on the research result concluded that Biology Learning in Excretion System in Humans Subject Matter in Class XI Madrasah Aliyah Negeri Barumun Tengah by Using Description, Interpretation, and Evaluation Learning Technique was very effective.